Thucydides and the ancient simplicity : the limits of political realism - Crane, Gregory, 1957- (Berkeley, Calif. : University of California Press, 1998)
Famous both as an analysis of power politics and as a classic of political realism, Thucydides' History of the Peloponnesian War is the earliest surviving realist text in the European tradition. From the opening speeches, Thucydides' Athenians emerge as a new and frightening source of power, oblivious to the rules and shared values under which the Greeks had operated for centuries. Gregory Crane shows how many of the assumptions that Thucydides attributed to his actors - and that seem commonplace to us today - boldly critique the operative assumptions of the archaic Greek elites. Crane's sophisticated claim for the continuing usefulness of the political examples of the classical past will appeal not only to classicists but to political scientists and anyone interested in the conflict between the exercise of political power and the preservation of human freedom and dignity.
1. Sherman at Melos -- 2. Truest Causes and Thucydidean Realisms -- 3. Representations of Power before and after Thucydides -- 4. Power, Prestige, and the Corcyraean Affair -- 5. Archaeology I -- 6. Archaeology II -- 7. The Rule of the Strong and the Limits of Friendship -- 8. Archidamos and Sthenelaidas -- 9. The Melian Dialogue -- 10. Athenian Theses.
Includes bibliographical references (pages 327-342) and index.
Print version record.
English.
JSTOR
Keywords: Thucydides -- Contributions in concept of truth; Thucydides; Thucydide -- Et le concept de vérité; Thucydide; Thucydides; History of the Peloponnesian War (Thucydides); Thucydides; Thucydides -- Political and social views; Thucydides; Thucydide (0460?-0395? av. J.-C.).; Thucydide, -- (0460?-0395? av. J.-C.) -- Contribution au concept de vérité.; Human behavior; Objectivity; Realism -- Political aspects; Political realism; Behavior; Comportement humain; Objectivité.; Réalisme politique; human behavior; HISTORY -- Ancient; POLITICAL SCIENCE -- History & Theory; Human behavior; Objectivity; Realism -- Political aspects; Truth; Historiae (Thucydides); Ethiek; Politieke filosofie; Greece -- History -- Peloponnesian War, 431-404 B.C.; Objectivité.; Réalisme -- Aspect politique; Grèce -- 431-404 av. J.-C. (Guerre du Péloponnèse)